Telaah Pustaka: Berbagai Metode dan Bahan Pembersihan Gigi Tiruan Lepas - Melisa Melisa (STOMATOGNATIC - Jurnal Kedokteran Gigi, 2023)
Cleaning of removable dentures is an important step to prevent cross-contamination and contribute to the health of the patient, the lifespan of the dentures, and the patient's overall quality of life. Bad dentures have undesirable effects such as bad breath, stains and biofilms, and calculus accumulation in the dentures which can lead to denture stomatitis, angular cheilitis, and poor oral health. A dentist is responsible for educating the patient after denture insertion so it will increase the knowledge of the denture wearer how to maintain the cleanliness of the denture properly. There are two methods for cleaning removable dentures, mechanically and chemically. Mechanical cleaning is done by removing plaque using a brush or ultrasonic cleaning. Meanwhile, chemically using chemical cleaning products such as hypochlrorite, peroxide, neutral peroxide dengan enzyme, enzyme, or acids. Recommended method for cleaning dentures is a combination method combining mechanical and chemical method.